Influence of microinclusion in life of rolling elements: Experimental, microstructural, analytical and numerical investigation. (October 2020) - Sesana, R.; Ossola, E.; Pagliassotto, S.; Rizzo, S.; Brusa, E.
Highlights: Proposal of a life model for bearing balls accounting for microinclusion properties. An experimental fatigue campaignrun on material and on balls. Eshelby-Mura model implementation for stress distribution around microinclusion. The contacts occurring for microinclusion is calculated for life estimation. Abstract: Rolling contact fatigue is the main cause of failure in bearings. Among other factors, damage phenomena are related to material properties and manufacturing processes. The damage evolution might be affected by microinclusions present in the material. This influence is related to composition, dimension, shape and location of microinclusions. The relation between microinclusions and fatigue life is investigated for both specimens undergoing rotating bending fatigue and balls undergoing Hertzian pressure fatigue for 100Cr6. A life model for balls, involving microinclusions effect and actual ball rotation movements is proposed. Failures are analyzed to relate life of rolling elements to the microinclusion parameters.